Investigation on the microstructure and mechancial properties of stellite 6 alloy printed by directed energy deposition - Ng, Jovian Wei Yan (Nanyang Technological University, 2024)
Additive manufacturing has revolutionised modern manufacturing process. Providing advantages in producing complex and customized objects layer by layer, offering design freedom and efficiency. Under the different methodologies of additive manufacturing, directed energy deposition has gained popularity particularly in industries requiring repair, modification, or the fabrication of large-scale metal components. Stellite 6 alloy is extensively used in the marine industry due to its exceptional resistance to corrosion due, wear, and high temperature. However, its inherent hardness and toughness pose challenges in fabrication, necessitating specialised equipment. Presently, powder metallurgy serves as the primary manufacturing method, involving sintering and additional heat treatments. This traditional method nonetheless has limitation in producing complex geometry and further machining is required and this will generate waste. To mitigate these challenges, directed energy deposition is explored for Stellite 6 alloy fabrication. This investigation aims to identify optimal process parameters to minimised defects and enhance mechanical properties. Following the DED process, the specimens with different processing parameters will undergo sample preparation for examination under OM and SEM. Through this experiment, it has been observed that increasing the laser power during DED, finer dendrites structure was observed. Laser power is closely related to the strength and hardness of the material. This study signifies a promising approach to address the drawbacks associated with traditional Stellite 6 Alloy manufacturing.